Nursing consultations to children in primary health care: a feedback of researched data - Daniele de Souza Vieira; Paloma Karen Holanda Brito; Leiliane Teixeira Bento Fernandes; Altamira Pereira da Silva Reichert (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To report the results of a dissertation developed with nurses who perform childcare consultations in Family Health Units in a Health District of João Pessoa, Paraíba, Brazil. Methods: Experience report of the presentation and interpretation of the research results, in 2018, with 42 nurses, using the conversation strategy with two focus groups. Results: The nurses showed disappointment with the negative results evidenced in the study's feedback, but they highlighted the importance of this moment for discussion and reflection of their practices, thus arousing the interest in qualifying the child's health care. Final considerations: This study achieved the objective of promoting the dissemination of the findings of a research, coupled with the social and ethical commitment to return to the nurses and participating services with the feedback of the research results to improve the reality in which they work.